A bandwidth-enhanced planar endfire antenna based on surface waves. Issue 14 (22nd September 2018) - Cheng, You-Feng; Ding, Xiao; Jin, Fu-Long; Shao, Wei
ABSTRACT: A surface-wave-based endfire antenna with an enhanced impedance bandwidth is presented in this paper. The antenna consists of a surface-wave guide (SWG) and five strips printed on the SWG. The endfire radiation benefits from the surface-wave diffraction of the SWG which is investigated with the Snell's law, effective surface impedance and eigenvalue analysis. A prototype is fabricated and measured, and the measured results indicate that the antenna has two resonances and its bandwidth is enhanced up to 16.1% (4.0–4.73 GHz). The proposed endfire antenna also exhibits high gain, good gain flatness, low cross-polarization level and low profile.